2000
DOI: 10.1677/joe.0.1640119
|View full text |Cite
|
Sign up to set email alerts
|

Ceiling culture of mature human adipocytes: use in studies of adipocyte functions

Abstract: Adipocytes contain large lipid droplets in their cytoplasm. When cultured, they float on top of the medium, clump together, and do not gain equal and sufficient access to the medium. Morphological changes cannot be observed and the majority of adipocytes undergo cell lysis within 72 h of isolation. We have used a ceiling culture method for human mature adipocytes which uses their buoyant property to allow them to adhere to a floating glass surface, where they remain viable for several weeks. Using confocal imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(105 citation statements)
references
References 32 publications
2
101
0
Order By: Relevance
“…PCR analysis showed that although DFAT cells had decreased level of LPL, leptin and glucose transporter 4 (GLUT4) compared with mature adipocytes, they still express key adipogenic markers including peroxisome proliferator-activated receptor gamma (PPARγ), CAAT/ enhancer-binding proteins (C/EBPα, C/EBPβ and C/EBPδ) and sterol regulatory element-binding protein-1c (SREBP1c) [14,[24][25]. In vitro, several recipes of adipogenic cultures were applied with different combination and dosage of induction chemicals such as dexamethasone, 3-isobutyl-1-methylxanthine and insulin transferring selenium X (ITS) [14][15]18]. Initial establishment of lipid droplets could found as early as 5-7 days of induction, while significant amount of lipid accumulation within cells could be observed after 2-3 weeks.…”
Section: Adipogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…PCR analysis showed that although DFAT cells had decreased level of LPL, leptin and glucose transporter 4 (GLUT4) compared with mature adipocytes, they still express key adipogenic markers including peroxisome proliferator-activated receptor gamma (PPARγ), CAAT/ enhancer-binding proteins (C/EBPα, C/EBPβ and C/EBPδ) and sterol regulatory element-binding protein-1c (SREBP1c) [14,[24][25]. In vitro, several recipes of adipogenic cultures were applied with different combination and dosage of induction chemicals such as dexamethasone, 3-isobutyl-1-methylxanthine and insulin transferring selenium X (ITS) [14][15]18]. Initial establishment of lipid droplets could found as early as 5-7 days of induction, while significant amount of lipid accumulation within cells could be observed after 2-3 weeks.…”
Section: Adipogenesismentioning
confidence: 99%
“…The adipocytes, other than the cell groups within the SVF portion, can be dedifferentiated into fibroblast-like cells named the dedifferentiated fat (DFAT) cells by ceiling culture strategy based on their buoyant property [13][14][15]. With this method and provided the fact that the mature adipocytes are the most abundant cell type in the adipose tissue, the DFAT cells which exhibit proliferation and multipotent capacity in vitro and in vivo have been regarded as an ideal source for adult postnatal pluripotent cells of much higher homogeneity than ASCs [14,[16][17][18][19].…”
mentioning
confidence: 99%
“…For more than 20 years it was clearly shown that in vitro-cultured mature unilocular adipocytes are able to become multilocular adipocytes and to undergo cell replication, 11 as it was confirmed later. 12 Because Ang II appears to have a trophic role in adipose tissue expansion, it may also contribute to the development of insulin resistance and type 2 diabetes. The improved insulin sensitivity and the reduced new-onset diabetes incidence in patients treated with angiotensin-converting enzyme inhibitors or AT1 receptor blockers 13,14 may be due to a 'brake' on the rate of VAT expansion.…”
Section: -6mentioning
confidence: 99%
“…Isolation of human fat tissue is being established as liposuction in plastic surgery and cosmetic surgery [15,16]. Human PAs can also be obtained by ceiling culture [17]. Our investigations may thus provide a basis for the treatment of patients by long-term supplementation of therapeutic protein without systemic immunosuppression.…”
Section: Discussionmentioning
confidence: 99%